2014
DOI: 10.1111/2049-632x.12133
|View full text |Cite
|
Sign up to set email alerts
|

Protease production byStaphylococcus epidermidisand its effect onStaphylococcus aureusbiofilms

Abstract: Due to the resistance of Staphylococcus aureus to several antibiotics, treatment of S. aureus infections is often difficult. As an alternative to conventional antibiotics, the field of bacterial interference is investigated. Staphylococcus epidermidis produces a serine protease (Esp) which inhibits S. aureus biofilm formation and which degrades S. aureus biofilms. In this study, we investigated the protease production of 114 S. epidermidis isolates, obtained from biofilms on endotracheal tubes (ET). Most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 34 publications
2
35
1
Order By: Relevance
“…Esp possibly degrades surface structures that help in providing the cohesive strength of S. aureus biofilms. Similar results were also shown by Vandecandelaere et al [35] where authors explained the role of S. epidermidis extracellular protease in inhibition of S. aureus biofilm formation both in vivo and in vitro. They have also demonstrated that although Esp protease degraded S. aureus biofilm matrix components, it did not affect oxidative metabolism of individual cells.…”
Section: Role Of Extracellular Proteases From Other Prokaryotes In DIsupporting
confidence: 89%
See 1 more Smart Citation
“…Esp possibly degrades surface structures that help in providing the cohesive strength of S. aureus biofilms. Similar results were also shown by Vandecandelaere et al [35] where authors explained the role of S. epidermidis extracellular protease in inhibition of S. aureus biofilm formation both in vivo and in vitro. They have also demonstrated that although Esp protease degraded S. aureus biofilm matrix components, it did not affect oxidative metabolism of individual cells.…”
Section: Role Of Extracellular Proteases From Other Prokaryotes In DIsupporting
confidence: 89%
“…Staphylococcus aureus biofilms treated with the protease containing supernatant from S. epidermidis were thinner and had almost no extracellular matrix. Also an increased survival of Caenorhabditis elegans was reported, when infected with S. aureus strains in the presence of S. epidermidis protease positive supernatant [35].…”
Section: Role Of Extracellular Proteases From Other Prokaryotes In DImentioning
confidence: 87%
“…Given that similar patterns of Aap processing are not observed in strains CSF41498 and 1457, these data suggest that the Aap B domains are unlikely to undergo spontaneous proteolysis. In this context, it is interesting that expression of the S. epidermidis serine protease Esp inhibits S. aureus biofilm formation and nasal colonization (44) and that levels of extracellular serine protease activity differ significantly among clinical isolates of S. epidermidis (45). Esp has been shown to process the major autolysin (46) and a range of proteins involved in S. aureus biofilm formation (47).…”
Section: Discussionmentioning
confidence: 99%
“…So far as know, the report about S. epidermidis isolates from the internal organs of the fish with antimicrobial activity against human pathogenic bacteria was rarely. Though, Vandecandelaere et al (2014) reported the S. epidermidis produced protease with obvious effects on S. aureus biofilms. Additional, the isolates of S. epidermidis TYH1 from Japanese fish-miso also produced a histidine decarboxylase, which were elucidated using native purified enzyme (Furutani et al, 2014).…”
Section: Strain S14 Identificationmentioning
confidence: 99%
“…The S. epidermidis as an opportunistic pathogen are the normal flora and the S. aureus are thought to be a primary target of food contaminate. It was well known that Staphylococci produced a wide range of antibacterial substances including bacteriocins, bacteriolytic enzymes, peptide antibiotics and polythiazoles (Vandecandelaere et al, 2014). S. epidermidis secreted various cytotoxins and enzymes, such as staphyolysin, enterotoxins, leukocidin, Toxic Shock Syndrome Toxin (TSST-1) and coagulase.…”
Section: Strain S14 Identificationmentioning
confidence: 99%